Perbandingan Pembiayaan Bank Muamalat Indonesia Sebelum dan Sesudah Pandemi Covid-19 - Budi Suharto; Muhammad Wardani Anwar; Fauzi Fauzi; Hendra Novian (Jurnal Ilmiah Ekonomi Islam, 2023)
The impact of Covid-19 on the movement of financing values, many have experienced a decline, including Bank Muamalat Indonesia. Before and during the Covid-19 pandemic, all financing values classified as productive assets at Bank Muamalat Indonesia experienced turmoil in their intermediary function which tended to decline. Changes that occur in the value of financing are a reflection of the performance of Bank Muamalat Indonesia itself and are a response to various external factors in Indonesia. This research formulated other problems, 1) How was the movement of financing products before the Covid-19 pandemic at Bank Muamalat Indonesia? 2) How was the movement of financing products during the Covid-19 pandemic at Bank Muamalat Indonesia? 3) Were there significant differences in financing products before and during the Covid-19 pandemic at Bank Muamalat Indonesia? The sampling technique used was purposive sampling. The amount of financing sampled in this study is limited to murabahah, istisna, qardh, mudharabah, musyarakah, and ijarah financing. The analytical method used is descriptive comparative analysis with data processing using the SPSS 25 program. In this study, the results obtained based on the paired sample t-test differed that there were significant differences in murabahah, istisna', qardh, musyarakah financing with successive values of 0.000, 0.000, 0.011, 0.045 and there were no significant differences in mudharabah financing before and during the Covid-19 pandemic with a value of 0.455. Meanwhile, the results of the Wilcoxon signed rank test for ijarah financing with a value of 0.028 indicate that there were significant differences before and during the Covid-19 pandemic at Bank Muamalat Indonesia.